Transparency as Trade Policy: Evidence from Notification Timing in TBTs - Irene Iodice (CESifo GmbH, 2025)
This paper quantifies the value of timely WTO notifications for Technical Barriers to Trade (TBTs). Using French firm-level export data, I find that advance notice halves the negative impact of TBTs on export participation, by reducing temporary exits and supporting entry, particularly among small and medium-sized firms. Exploiting variation in notification delays, I show that this effect operates by reducing uncertainty about compliance costs, rather than by giving firms more time to adjust. A theoretical framework with firm heterogeneity and trade policy uncertainty formalizes this mechanism: notification lowers uncertainty, reducing firms' incentives to delay or suspend exports. The quantitative importance of this effect is equivalent to avoiding a tariff increase of up to 28 percentage points.
Keywords: F13; F14; D84; 330